Música e deficiência visual: uma proposta de ensino e aprendizagem online de violão para pessoas cegas - Costa, Luiz Fernando Navarro (2023)
Online teaching has become an increasingly popular and practical alternative to traditional classroom teaching, particularly for students living in remote locations or with physical disabilities. This research implements and evaluates the effectiveness of an online guitar course for students who suffer from complete blindness. The objective is to understand the teaching processes, potential methods, challenges and effectiveness of delivering online education to blind students. The motivation for undertaking these research – developed at the Post-graduate Program in Music at Universidade Federal da Paraíba/UFPB (Federal University of Paraíba) – was triggered by a personal experience of teaching guitar to a blind female student. The theoretical references involved two theme-axes: 1) Musical education and visual impairment; 2) Online music teaching. As an essentially multi-disciplinary work, these theme-axes had connections with other areas and sub areas, such as: Health, Psychology, Information and Communication's Technology, Assistive Technology, Inclusion, among others. The methodology deployed was action-research. The process of pedagogical intervention consisted of an online guitar course for blind people, held in two phases: the first with ten weekly individual lessons, from October to December 2020. The second phase, which started in March and ended in June 2021, comprised of a monthly collective lesson, with a total of fourteen individual and four collective lessons. Both phases had the same participants: five blind students from different undergraduate courses at UFPB. Three students were beginners and two already reported some experience playing the guitar. The Online Guitar Course for the Blind (OGCB) offered by UFPB's extension program, focused on the practice of popular guitar but did not make use of braille musicography. The platform chosen for the synchronous classes was Google Meet, accessed by the students through smartphones. For the asynchronous interactions in files and links' sharing, the course used WhatsApp and YouTube platforms. Several tutorials in video format were prepared specifically for the course, focusing on certain elements of the tutorial. The results of the action-research method showed the effectiveness of the online guitar teaching for blind people. Although some difficulties were experienced due to a slow internet connection, occasionally compromising a good follow-up of the students' activities, delivering an effective course has been proven to be possible – with satisfactory technological resources and by deploying an appropriate methodology – to teach, in an online modality, popular guitar for blind people. The students use the digital technologies without any issues, independently accessing the platforms as required. Guitar learning was based mainly on textile memory and listening, complemented by the methodology of the course which used alternative conventions and systems for teaching rhythm, chords, and how to use ciphers in songs' harmonization. The beginners learned how to accompany the songs and Brazilian rhythms planned for the pedagogical intervention. For the experienced students, the course was an opportunity to recycle their guitar knowledge and to get to know new accessibility systems for practicing popular guitar. The students found the interactions motivating, fostering collaborative learning, as well as helping them to face the difficult days of the Covid-19 pandemic. Although online guitar teaching is currently restricted mostly to those who can see, the OGCB was a unique experience that sought to contribute to the equity of the visually impaired population.